Determination of lipid content and stability in lipid nanoparticles using ultra high‐performance liquid chromatography in combination with a Corona Charged Aerosol Detector. Issue 9 (21st December 2021) - Kinsey, Caleb; Lu, Tian; Deiss, Alyssa; Vuolo, Kim; Klein, Lee; Rustandi, Richard R.; Loughney, John W.
Abstract: For many years, lipid nanoparticles (LNPs) have been used as delivery vehicles for various payloads (especially various oligonucleotides and mRNA), finding numerous applications in drug and vaccine development. LNP stability and bilayer fluidity are determined by the identities and the amounts of the various lipids employed in the formulation and LNP efficacy is determined in large part by the lipid composition which usually contains a cationic lipid, a PEG‐lipid conjugate, cholesterol, and a zwitterionic helper phospholipid. Analytical methods developed for LNP characterization must be able to determine not only the identity and content of each individual lipid component (i.e., the parent lipids), but also the associated impurities and degradants. In this work, we describe an efficient and sensitive reversed‐phase chromatographic method with charged aerosol detection (CAD) suitable for this purpose. Sample preparation diluent and mobile phase pH conditions are critical and have been optimized for the lipids of interest. This method was validated for its linearity, accuracy, precision, and specificity for lipid analysis to support process and formulation development for new drugs and vaccines.